Analisis Orientasi Kewirausahaan Terhadap Kinerja Pemasaran Melalui Keunggulan Bersaing - Suwendi Suwendi; Erry Sunarya; Nor Norisanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study was conducted to determine the influence of the Entrepreneurial Orientation variable and the Competitive Excellence variable on Marketing Performance on Chicken Porridge UMKM actors in Sukabumi City. The research method used in this study is a descriptive, associative research method with a quantitative approach. The population in this study is 146 members registered with the Sukabumi City Discoperindag. And for the sample is all members of the population using the slovin formula. Using IBM SPSS software version 29, as a data analysis technique tool. The results of this study showed that one hypothesis was accepted and one was rejected. And it can be interpreted that there is a positive and significant influence between entrepreneurial orientation on marketing performance, but competitive advantage as a mediator does not succeed in mediating entrepreneurial orientation variables to competitive advantage variables.